Perancangan Sistem Informasi Berbasis Web Pada Oemah Kucek Laundry - Noor Meilinda; Fitria Risyda; Yulisa Gardenia (Jurnal Mahasiswa Informatika dan Desain, 2025)
The development of information systems has undergone many changes, which is inseparable from the increasingly rapid technological developments in the current era of globalization which can affect many aspects and encourage competition between companies to develop their business and seek goods or services sold on the market following company goals. Oemah Kucek laundry is one of the businesses engaged in the service of washing and ironing clothes. Services at Oemah Kucek laundry are currently still done conventionally and simply not using a computerized system. Oemah Kucek laundry needs a program design that can help simplify and speed up every service process and make it easier to manage laundry financial reports. Making this system is designed using PHP as the programming language, and using MySQL as the database. The results of this study are in the form of an information system, with the laundry service information system, is expected to improve service quality which has an impact on increasing Oemah Kucek Laundry's income.